Tensions and conflicts between life and work on contemporary capitalism - Rosemary Roggero (Universidade Federal de Santa Maria, 2013)
This paper questions the possibility of releasing the subjectivity, in the tension between life and work, which constitutes the professional qualification. It analyzes the similarities between training and work, towards a self-awareness and social consciousness in the context of culture. This study also notes how the concept of competence points to training processes aimed at mere adaptation to the capitalist logic, reducing life to work.